Влијание на социоемоционалното приврзување врз личноста и сликата за себе кај младите со анксиозни растројства - Наумовска, Андромахи (Медицински факултет, УКИМ, Скопје, 2015)
Introduction: Attachment is a primary need for bonding of one individual with another and creating positive relation with that other. Positive attachment allows feelings of protection. The “self” concept (self image and self esteem) integrates the experience of one's own traits and the relations in its social environment, these are vital to the development of the individual's personality. Late adolescence, as the last stage of adolescence, is particularly important for the development of identity, self image and self esteem, and integrity of the person as a whole. Unfinished development tasks in late adolescence lead to delayed or prolonged adolescence and anxiety issues. Epidemiological studies indicate that anxiety disorders are among the most common psychiatric disorders that cause substantial disruption of the psychosocial functioning of the individual; they can lead to social maladjustment and dysfunction within the immediate and wider social environment. Aim: The main goal of this study is to determine the impact of attachment on the personality, self image and self esteem in young people with anxiety disorders. Material and method: The survey has been conducted in the Psychiatric Hospital "Skopje" - Skopje, Center for Mental Health - "Center" and Psychiatric Clinic - Skopje, on a representative sample of 120 young people with anxiety disorders and 120 young people without psychiatric disorders in the control group (18-30 yr.). The following questionnaires have been used in the research: Demographical questionnaire, Taylor Manifest Anxiety Scale (TMAS), Hamilton Anxiety Scale (HAM-A), the appropriate scale for anxiety disorder (Scale for Generalized Anxiety Disorder (GAD7), Social Phobia Scale (SPIN) or Scale for Panic Disorder (PDSS)), Offer Self Image Questionnaire (OSIQ), Coopersmith Self Esteem Questionnaire (CSE), Questionnaire for Personality Traits (BTS) and Adult Attachment Questionnaire (ASQ). Results: Childhood attachment affects personality traits, which further affects the self concept, self image and self respect, and these vary among young people with various anxiety disorders. The findings of this study are expected to apply in the creation of appropriate therapeutic programs for anxiety disorders, they would be age-specific and the personality, self image and self esteem of the individual would be taken into consideration in order to prevent recurrence of the anxiety disorder. They would also help create appropriate programs to improve family functioning and programs for more efficient reintegration of the individual into society.
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Марија Ралева.
Keywords: anxiety disorders, attachment, personality, self image, self esteem, young people, late adolescence